Comparison Study of Functional Capacity in Revascularized STEMI and Nonrevascularized NSTEACS Patients Using the 6-Minute Walk Test - WN Adriyawan (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Background: Coronary artery disease generally demonstrates decrease of maximal uptake of ....